Volume 5: Ocean Space Utilization; Ocean Renewable Energy 2011
DOI: 10.1115/omae2011-49563
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Response of an Offshore Wind Turbine With Realistic Flexibility to Breaking Wave Impact

Abstract: The effects of operational loads and wind loads on offshore monopile wind turbines are well understood. For most sites, however, the water depth is such that breaking or near-breaking waves will occur causing impulsive excitation of the monopile and consequently considerable stresses and displacements in the monopile, tower and turbine. To investigate this, pilot model tests were conducted with a special model of an offshore wind turbine with realistic flexibility tested in (extreme) waves. This flexibility wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The numerical values for each event are given in Table 5. These observations suggest, as was also found in de Ridder et al (2011), that not taking into account the 2 nd mode of the structure when assessing ULS leads to underestimation of the total response. For these 21 events, we also note that the maximum response is negative, i.e.…”
Section: Contributions To the Total Responsesupporting
confidence: 76%
See 1 more Smart Citation
“…The numerical values for each event are given in Table 5. These observations suggest, as was also found in de Ridder et al (2011), that not taking into account the 2 nd mode of the structure when assessing ULS leads to underestimation of the total response. For these 21 events, we also note that the maximum response is negative, i.e.…”
Section: Contributions To the Total Responsesupporting
confidence: 76%
“…In addition to higher order hydrodynamic loads, breaking wave events have been a major concern for offshore structures. Both de Ridder et al (2011) and Bredmose et al (2013) carried out experiments on a bottom-fixed responding structure (as opposed to a stiff structure) whose characteristics were similar to those of an idling extra-large wind turbine (i.e. with the blades completely pitched to feather to limit the aerodynamic loading) and found that breaking waves could lead to extreme accelerations of the nacelle.…”
Section: Introductionmentioning
confidence: 99%
“…Hence in these cases, hydrodynamic tests can be carried out without the rotor as long as the influence of the rotor mass properties is correctly represented (e.g. De Ridder et al, 2011).…”
Section: Uncoupled Testsmentioning
confidence: 99%
“…More extensive testing was carried out at MARIN [11]. A 1:30 flexible model was constructed to represent the mass, stiffness, and first two modes of a 6MW wind turbine with 6 m diameter at the waterline (full scale).…”
Section: Facilitymentioning
confidence: 99%